The afterlives of transitional justice - Zvobgo, Kelebogile (International journal of transitional justice, 2025)
Rising authoritarianism, far-right parties and violent political movements in the 21st century prompt scholars and practitioners to revisit two foundational assumptions in the transitional justice field, which was established in the 20th century amid the third wave of democratization. The first is that transitional justice is a consequence and a cause of democratic transition and consolidation. The second is that transitional justice has been a successful global project. Current political developments challenge us to take stock of the field and consider the implications for current and future scholarship and practice. In this introduction to the ‘Afterlives of Transitional Justice’ special issue of the International Journal of Transitional Justice (IJTJ), we first reflect on the many forms (‘lives’) that transitional justice has taken over the decades. The contributions address transitional justice’s life in three ways: as the transition to democracy, as the tools and processes themselves and as an academic and practice field. We then consider evolution and change in transitional justice (‘afterlives’). In increasingly perilous times for human rights, we hope that the insights gathered in these pages will help affected communities, activists, practitioners, policymakers and scholars look back in order to move forward and uphold the promise ‘Never again!’